PENGARUH PENGEMBANGAN KARIR DAN INSENTIF TERHADAP KINERJA KARYAWAN PT. MATAHARI DEPARTEMENT STORE JENDERAL URIP PONTIANAK - Oktaviani, Rinsan Lestari; Achmadi, Achmadi; Basri, Muhammad (Universitas Tanjungpura, 2023)
The .goal of thiis research wias to see how careier development and incentiives affected emplloyee performance at PT Mata.hari Departmeint Store Jenderal Uriip Pontiianak. The research approach employed is quantitative research utilizing descriptive methods.